Pengaruh Kualitas Website (Webqual 4.0) Terhadap Penggunaan Kembali - Prayogo, Arifyan Dwi; Sutisna, Mamun (Jurnal Riset Bisnis dan Investasi, 2017)
This study assesses the effect quality of the website Tokopedia using WebQual 4.0 on repeat usage of website services (study on tokopedia website users). The purpose of this study was to analyze the influence of tokopedia website quality on repeat usage which context is e-commerce. Tokopedia growth until the end of 2016 made them as a refresher in C-to-C Commerce which has the modern services that gather buyers and sellers without face to face interaction so website platform of tokopedia has important role in tokopedia business activity. The research method using descriptive analysis with quantitative approach. Method for data analysis are using descriptive analysis, classical assumption test, correlation analysis, simple regression analysis, and hypothesis test. Sample on this research are 200 respondents which is users of tokopedia. Based on the results of data, website quality is in good category and repeat usage is in fair category. The conclusion of this research is there is influence of website quality on repeat usage is equal to 40,6%.